Використання гіпотези λ-компактності при побудові навчаючої вибірки для прогнозуючих нейромережевих моделей - Krisilov, V. А.; Yudin, S. А.; Oleshko, D. M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The problem of forming a qualitative training sample for neural networks in forecasting is solved. The possibility of use the hypothesis of λ-compactness at the step of forming an ensemble of recognizable classes is described. An advanced algorithm of forming a qualitative training sample is offered on the basis of the mechanisms considered.